A competing motivation (Ökologisches Wirtschaften - Fachzeitschrift, 2019)
Although environmental awareness is a strong motivation, even for highly engaged individuals it has to compete with other motivations in guiding behaviour. A process-oriented approach to this dilemma allows for alternative behaviour and continuous engagement. That approach might be transferred also to organizational units.